Diiodido[N′-(2-methoxybenzylidene)-N,N-dimethylethane-1,2-diamine]zinc(II) - Xue-Wen Zhu (Acta Crystallographica Section E, 2009)
In the title complex, [Zn(C12H18N2O)I2], the ZnII ion is four-coordinated by the imine N and amine N atoms of the Schiff base ligand and by two iodide ions in a distorted tetrahedral coordination.